Reducing Poverty on a Global Scale: Learning and Innovating for Development : Findings from the Shanghai Global Learning Initiative. - Moreno-Dodson, Blanca (World Bank e-Library., 2005)
In 2003 the World Bank, in partnership with the Government of the People's Republic of China, began a one year-long global learning process that focused on worldwide efforts to reduce poverty along different dimensions. A series of case studies, multi-country interactive videoconferences, online dialogues, and field visits led up to the working conference in Shanghai, on May 25 - 27, 2004. Development lessons and experiences were shared and debated at this event by policymakers, politicians, donors, academics, development practitioners, civil society groups, and representatives from developmen.